Length and caliber of the rectosigmoid colon among patients with Chagas disease and controls from areas at different altitudes - Lopes,Gesner Pereira (2013)
Introduction In this study, we investigated radiological changes in the sigmoid colon in chagasic patients by comparing their colon lengths and caliber with those of non-chagasic living in the same region and non-chagasic living at high altitudes. Methods A total of 317 individuals were evaluated using clinical, serological and radiological methods and divided into three groups: 1) one hundred and nine non-chagasic individuals from Uberaba, Brazil; 2) sixty-one non-chagasic from Puno, Peru; 3) one hundred forty-seven chagasics examined in Uberaba, being 62 without megacolon (3A), 72 with megacolon (3B) and 13 with doubtful diagnosis of megacolon (3C). Results In group 2, the sigmoid colon had a significantly larger caliber (p=0.001) and the rectosigmoid colon was longer (p<0.001) than group 1. In subgroup 3A, the sigmoid colon (p<0.001) and rectum (p<0.001) had a significantly larger caliber and the rectosigmoid was longer (p<0.001) than that of the non-chagasic individuals. In subgroup 3B, the rectosigmoid was longer in all patients, and the caliber of the sigmoid was significantly larger than that of subjects in subgroups 3A and 3C (p<0.001). Conclusions Morphometric analysis confirms that Chagas disease may increase the caliber and length of the rectosigmoid. Our results suggest that altitude, ethnicity and diet may have influenced the size and length of the rectosigmoid of andean patients.